2023
DOI: 10.1037/pag0000733
|View full text |Cite
|
Sign up to set email alerts
|

Do associations between sense of purpose, social support, and loneliness differ across the adult lifespan?

Abstract: Past research has suggested that the path to purpose involves connections with people along the way. In support, sense of purpose appears higher amongst those adults with more positive social relationships and interactions. However, research has yet to consider whether associations between sense of purpose and social relationship variables differ across adulthood. The present study examined this claim using a sample of Swiss adults, who completed measures for sense of purpose, loneliness, received support, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Furthermore, there are research showing that factors making life meaningful change as people age. While the relation between loneliness and purpose in life remained stable in their study, Hill et al (2023) found that age moderated the association between sense of purpose and social support, with support being less important for older adults' purpose in life. Hicks et al (2012), in turn, demonstrated that those who expect to have less lifetime left draw more meaning from the present.…”
mentioning
confidence: 78%
“…Furthermore, there are research showing that factors making life meaningful change as people age. While the relation between loneliness and purpose in life remained stable in their study, Hill et al (2023) found that age moderated the association between sense of purpose and social support, with support being less important for older adults' purpose in life. Hicks et al (2012), in turn, demonstrated that those who expect to have less lifetime left draw more meaning from the present.…”
mentioning
confidence: 78%
“…However, purpose in life or other social factors (e.g., marital status, contact with children or other family members) did not emerge as significant mediators [ 6 ]. Purpose in life declines sharply in older ages, perhaps due to role changes (e.g., retirement) [ 45 , 46 ], and correlations between purpose in life and social support and loneliness are weaker among older adults relative to emerging and midlife adults [ 47 ]. Taken together, it may be that purpose in life is most relevant as a mediator of R/S and mortality links in midlife (i.e., the MIDUS sample) as compared to older ages (i.e., the HRS sample).…”
Section: Discussionmentioning
confidence: 99%